The evaluation of land suitability to arabica coffee (Coffea arabica) and strawberry (Fragaria vesca Linn.) in Pematang Sidamanik Subdistrict of Simalungun District. - Usmul Safti Kartika; posma marbun (Jurnal Agroekoteknologi, 2016)
The objective of this research is to evaluatethe land suitability arabica coffee (Coffea arabica) and strawberry  (Fragaria vescaLinn.) in Pematang Sidamanik Subdistrict of Simalungun District.The methode of this research is the survay method. from the results of the overlay  from the map of  soil types, map of  topography, and map of height place, retrieved 10 (ten) units of land use map. The result of the research showed that  actual and potential land suitability class for arabica coffee and strawberry  at SPL 1, 2, 3, 4, 5, 6, 8, 9 is Not Suitable (N) with restrain factor is rooting condition (rc).  The actual land suitability class for  arabica coffeeat SPL 7 is Not Suitable (N) with restrain factor is erosion hazard (eh). SPL 10 is Marginally Suitable (S3) with restrain factors water available, nutrient retention, and erosion hazard (wa, nr, eh), while the potential land suitability class at SPL 7 is Marginally Suitable (S3) with restraint factor water available and erosion hazard (wa, eh). SPL 10 is Marginally Suitable (S3) with restrain factor water available (wa).The actual land suitability class for   strawberry  at SPL 7 is Not Suitable (N) with restrain factor is erosion hazard (eh). SPL 10 is Marginally Suitable (S3) with restrain factor  nutrient retention and erosion hazard (nr, eh), while the potential land suitability class for strawberry  at SPL 7 is Marginally Suitable (S3) with restrain factor erosion hazard (eh). SPL 10 is Fairly Appropriate (S2) with restrain nutrient retention (nr, eh). Keywords : Land suitability, arabica coffee, strawberry